3- Sociological and Anthropological Training in Ethiopia - Admassie, Yeraswork; Yntiso, Gebre (African Sociological Review, 2006)
Formal training in sociology and social anthropology in Ethiopia has a relatively long history, having commenced under the University College of Addis Ababa (UCAA) established in 1951.2 In this relatively long period of time, training in sociology and social anthropology has passed through many stages. Courses in the two related disciplines have been offered in various forms being packaged in one undergraduate programme. The organisational structure within which undergraduate level training in sociology and social anthropology is placed has mutated and assumed a number of forms that were accompanied by successive revisions of curriculum. For these reasons, the paper offers a brief overview of the evolution and development of sociological and anthropological training in Ethiopia over the last 55 years before moving on to discuss current programmes and activities.